Pengaruh Modal Sosial dan Keterdedahan Informasi Inovasi terhadap Tingkat Adopsi Inovasi Jagung di Kabupaten Lombok Timur Nusa Tenggara Barat - Yohanes G. Bulu; Sunarru S. Hariadi; Ageng S. Herianto; nFN Mudiyono (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2009)
EnglishThe objectives of this research are:1) analyses the influence of exposure innovation information, human capital, innovation promotion, and rate of adoption of corn innovation toward social capital; and 2) analyses the influence of social capital, exposure innovation information, human capital, and innovation promotion toward rate of adoption of corn innovation. The research was conducted in East Lombok Regency, West Nusa Tenggara Province, from July to October 2008. The research it used survey method with combining quantitative and qualitative approaches. Data of the research were collected through an in-depth interview on 220 respondents and 12 informants. Based on result of the research, it is concluded that social capital was significantly influenced by factors such as the innovation communication frequency, innovation communication intensity, work motivation, farmer’s attitude, innovation economic benefit value, market availability, and rate of adoption of corn innovation. The factors was significantly influenced toward rate of adoption of corn innovation were social capital, information access of innovation, innovation availability, and market availability. However, in adoption process of corn innovation, farmer’s exposure toward innovation information, human capital, and innovation promotion worked through the social capital. The capital is one of the factors required to consider in improving the adoption of corn innovation, so the revitalization of social capital should be done by using various of cohesively approaches. IndonesianTujuan penelitian ini adalah untuk 1) menganalisis pengaruh keterdedahan informasi inovasi, modal manusia, promosi inovasi, dan tingkat adopai inovasi jagung terhadap modal sosial dan 2) menganalisis pengaruh modal sosial, keterdedahan informasi inovasi, modal manusia, dan promosi inovasi terhadap tingkat adopsi inovasi jagung. Penelitian ini dilakukan di Kabupaten Lombok Timur, Nusa Tenggara Barat, dari bulan Juli - Oktober 2008. Penelitian menggunakan metode survai dengan mengkombinasikan pendekatan kuantitatif dan kualitatif. Data dikumpulkan melalui wawancara mendalam pada 220 responden dan 12 orang informan. Berdasarkan hasil penelitian ditemukan bahwa modal sosial dalam adopsi inovasi jagung dipengaruhi oleh faktor frekuensi komunikasi inovasi, intensitas komunikasi inovasi, motivasi kerja, sikap petani, nilai manfaat ekonomi inovasi, ketersediaan pasar, dan tingkat adopsi inovasi. Faktor-faktor yang berpengaruh nyata terhadap tingkat adopsi inovasi jagung adalah modal sosial, akses informasi inovasi, ketersediaan inovasi, dan ketersediaan pasar. Bagaimanapun dalam proses adopsi inovasi jagung bahwa keterdedahan petani terhadap informasi inovasi, modal manusia, dan promosi inovasi adalah bekerja melalui modal sosial. Modal sosial merupakan salah satu faktor yang perlu dipertimbangkan dalam peningkatan adopsi inovasi jagung, sehingga sangat perlu untuk melakukan revitalisasi modal sosial dengan menggunakan berbagai pendekatan secara kohesif.